No Science in Politics: A Qualitative Content Analysis of Industrial Hemp Production in Florida Newspapers - Kevin W Kent; Jarred A Shellhouse; Angela B. Lindsey; Lisa K Lundy (Journal of Applied Communications, 2021)
This study examined how Florida newspapers framed the topic of industrial hemp production before and after the 2019 state legislative session. A total of 34 articles from the state’s largest newspapers were reviewed using qualitative content analysis to discover what frames were used, what scientific sources were cited, and what opinion leaders were quoted in the discussion of industrial hemp production. The analysis revealed the most frequently used frames within the study’s timeframe focused on politics or economic potential. Only one article cited science-based information. A majority of quotes were from political leaders and policy makers. Future research should be conducted to explore the frames used in other forms of media, including social media (i.e. Twitter), especially related to controversial trend topics like industrial hemp production.
Keywords: industrial hemp production; science communication; agricultural policy